The Role of Employee Engagement Mediates the Relationship of the Work Environment, Teamwork on Employee Performance - Paulino Mendonca; I Gede Riana; Augusto da Conceição Soares (ABM: International Journal of Administration, Business and Management, 2020)
Paulino Mendonca, Master Program in Management Sciences, Magister Program Institute of Business IOB. The Role of Employee Engagement Influence Work Enviroment, Teamwork on Employee Performance. Commission of Supervisor I: Dr. I Gede Riana, SE., MM, Commission of Supervisor II: Dr. Augusto Da C. Soares, SE., MM. This study aims to analysis (1) influence of the work environment on employee performance, (2) influence of the work environment on employee involvement, (3) influence of teamwork on employee performance, (4) influence of teamwork on employee involvement, (5) the effect of employee involvement on employees performance, (6) the role of employee involvement mediates the working environment relationship on employee performance, (7) the role of employee involvement mediates teamwork relationship to employee performance. The population in this study was 680 of all MAP employees at the Dili, the sample using the slovin formula so as to get 156. Data were analyzed using the Smart-PLS The research findings the work environment, teamwork, influence positive not significantly to employee performance. This research shows that work environment, teamwork is not able to improve employee performance. The effect of work involvement on employee performance found that involvement had a positive significant effect on employee performance. The role of employee involvement mediates the working environment relationship, teamwork is full mediation. Keywords: Work Environment, Teamwork, Employee Engagement, Employee Performance.